Design and Implementation of Web-Based Helpdesk Information Systems Using Extreme Programming Methods - Freddy Wicaksono; Orin Satriani Baswara (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2020)
Technological developments have become a necessity for job optimization, be it desktop, web or mobile-based software, of course this really supports work with fast, timely completion, without spending a lot of effort and money. The Help Desk is a facilitator for the process of solving operational problems, through communication and interaction networks, internal and external, between the source of the problem (the client) and the potential / problem solving analysis capacity (experts) so that the Asset Management process becomes more effective in improving unit performance. Its operational implementation refers to the principles in the concept of Knowledge Management. Extreme programming is a method that lightens the burden or speeds up the software development process, the characteristics of this method are in accordance with this study which has a small number of team members. This method is flexible so that it can adapt to the changes that customers want. With this the user becomes easier for system development